Anticancer Drug-Induced Cardiotoxicity: Insights and Pharmacogenetics - Archana Adhikari; Syed Mohammed Basheeruddin Asdaq; Maitham A. Al Hawaj; Manodeep Chakraborty; Gayatri Thapa; Nihar Ranjan Bhuyan; Mohd. Imran; Mohammed Kanan Alshammari; Mohammed M. Alshehri; Aishah Ali Harshan; Abeer Alanazi; Bushra Dhuhayyan Alhazmi; et al. (MDPI AG, 2021)
The advancement in therapy has provided a dramatic improvement in the rate of recovery among cancer patients. However, this improved survival is also associated with enhanced risks for cardiovascular manifestations, including hypertension, arrhythmias, and heart failure. The cardiotoxicity induced by chemotherapy is a life-threatening consequence that restricts the use of several chemotherapy drugs in clinical practice. This article addresses the prevalence of cardiotoxicity mediated by commonly used chemotherapeutic and immunotherapeutic agents. The role of susceptible genes and radiation therapy in the occurrence of cardiotoxicity is also reviewed. This review also emphasizes the protective role of antioxidants and future perspectives in anticancer drug-induced cardiotoxicities.